STRATEGI KOMUNIKASI PEMASARAN PRODUKSI PERTANIAN JAMUR TIRAM PADA KELOMPOK TANI “ANUGERAH MAKMUR” DI DUSUN CIBUERIUM, SERANGPANJANG, KABUPATEN SUBANG - ARI SULISTYANTO; DWINARKO; TABRANI SJAFRIZAL; SAEFUL MUJAB (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The limited knowledge of marketing faced by the "Anugerah Makmur" farmer group in Cibuerium Hamlet, Pongang Village, Kec. Serangpanjang, Kab, Subang in cultivation "Oyster Mushrooms cause excess production of Oyster Mushrooms can not be marketed to the fullest. So far, marketing has relied on local middlemen who can only market in limited quantities in the market area of ​​Seranpanjang District. Through the activities of the Community Partnership Program (PKM) encourage increased knowledge and management capabilities of marketing communications that are integrated and integrated as well as understanding of modern and export-oriented marketing management. Through training and mentoring methods, it is expected that, first, the ability in managing integrated marketing communications, starting from the stage of improving the quality of production. Second, the ability to manage the distribution of oyster mushroom production. Third, the ability to manage production pricing strategies. Fourth, the ability to manage promotions, both direct marketing and various promotion strategies